METHODOLOGICAL APPROACH TO CONGRUENCE OF QUADRILATERALS IN HYPERBOLIC GEOMETRY - Milan Zlatanović; Victor Aguilar (Facta Universitatis. Series, Teaching, Learning and Teacher Education, 2021)
In this paper we will prove new criteria for the congruence of convex quadrilaterals in Hyperbolic geometry and consequently, display the appropriate methodological approach in teaching the same. There are seven criteria for the congruence of hyperbolic quadrilaterals, while there are five for the congruence of Euclidean quadrilaterals. Using a comparative geometric analysis of quadrilateral congruence criteria in Euclidean and Hyperbolic geometry we described all possible cases and made a methodological approach to the problem. The obtained results can influence the approaches to the study of these contents with students in the hyperbolic geometry teaching.